Phosphorus response of maize grown on alfisols of southern Nigeria - Kang, B.T.; Osiname, O. A. (Wiley, 1979)
Phosphorus plays an important role for food crop production in the forest zone of tropical Africa but very little information is available on the phosphate requirement for maize production there. Field trials were, therefore, conducted with maize (Zea mays L.) at two locations on Alfisols in southern Nigeria to investigate the P response and the residual effect of applied P. The experimental sites were recently cleared from fallow and the vegetation was removed after land clearing. On the Egbeda soil (Oxic Paleustalf), which is derived from basement complex rocks, five seasons of maize croppings were done from 1971 to 1973 using a split-plot design with three replications. Four periods of fresh P applications (major and minor seasons 1971 and major and minor seasons 1972), formed the main plots and each of these fresh P applications consisted of five P rates (0, 26, 52, 78 and 104 kg P/ha) which made up the sub-plots. Maize culture T2A ✕ TZB was planted at a spacing of 75 ✕ 25 cm (53,300 plants/ha). The minor season maize received supplementary irrigation. On the Alagba soil (Oxic paleustalf) which is derived from sedimentary rocks, five P rates (0, 20, 40, 80, and 160 kg P/ha) were compared using a randomized complete block design with four replications. Phosphate was broadcasted as single superphosphate and incorporated in the soil to the various treatments. The residual effects of applied P were followed up at both locations. With removal of fallow vegetation following land clearing, significant responses to P applications were observed at both locations. The P requirement for obtaining significant yield increases was not very high, ranging from 26 to 52 kg P/ha depending on season and location. Higher yield response to P was observed during the main season (April to July) than during the minor season (August to November) planting. At both locations significant residual effects of applied P was observed on maize yield and Bray P-1 soil test levels. On the Egbeda soil it was possible to build up and maintain adequate amounts of extractable P for two to three maize crops with one addition between 52 to 104 kg P/ha. Good relationship was observed between maize grain yield and Bray P-1 test values on the Egbeda soil. The critical Bray P-1 test values was estimated to be about 14 ppm P. Results of incubation studies showed that under laboratory conditions 2.5 to 3 ppm of fertilizer P was required to increase the Bray P-1 test level by 1 ppm for the Egbeda and Alagba soils respectively. Under field conditions for the Egbeda soil the P rate required was estimated to be 3.5 ppm P. The critical P in the ear leaf was estimated at 0.3% P. High rate of P application was shown to depress the Zn status in the ear leaf.